Ketidakadilan vertikal dalam peneteapan pajak bumi dan bangunan: Kasus Yogyakarta - Jaya, Samon (Economic Journal of Emerging Markets, 2016)
The problem faced by the government to impose property tax is the market value of the property (NJOB). This leads unfair assessment. Generally, NJOP tends to be a regressive vertical unfair.